2021
DOI: 10.1039/d1sc00664a
|View full text |Cite
|
Sign up to set email alerts
|

Ground- and excited-state dynamic control of an anion receptor by hydrostatic pressure

Abstract: Hydrostatic pressure can control interactions of chiral countercations with helical receptors containing anions, causing remarkable chiroptical changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 78 publications
1
12
0
Order By: Relevance
“…As listed in Table S1 in the ESI,† the calculated shifts as a function of hydrostatic pressure ranged from −0.658 to −0.760 cm −1 MPa −1 for absorption and from −0.775 to −1.129 cm −1 MPa −1 for fluorescence, respectively. These slopes are almost equal to those observed in the previous reports, 37–45 indicating that the pressure-dependent spectra of HA s turned out to behave like common π-chromophores.…”
supporting
confidence: 80%
See 1 more Smart Citation
“…As listed in Table S1 in the ESI,† the calculated shifts as a function of hydrostatic pressure ranged from −0.658 to −0.760 cm −1 MPa −1 for absorption and from −0.775 to −1.129 cm −1 MPa −1 for fluorescence, respectively. These slopes are almost equal to those observed in the previous reports, 37–45 indicating that the pressure-dependent spectra of HA s turned out to behave like common π-chromophores.…”
supporting
confidence: 80%
“…Nevertheless, study on hydrostatic pressure effects in homogeneous solutions is a quite old topic, and ground-state equilibria and excited-state rates upon hydrostatic pressurization have been investigated for a long while since the early 1960s, 21–34 provided that the high-pressure solid chemistry using diamond anvil cells 35,36 is excluded herein. In fact, we have also revealed that the luminescent characters of mechanophores/fluorophores/chromophores, 37–41 solvatochromism of Reichardt's dye, 42 and chiroptical properties of chiral materials 43–45 are controllable by hydrostatic pressure. In particular, the tetraphenylethylene-tethered polymers showed ratiometric fluorescence responses against hydrostatic pressure parameters.…”
mentioning
confidence: 83%
“… Ground- and excited-state dynamic control of an anion receptor by hydrostatic pressureKinoshitaT.HaketaY.MaedaH.FukuharaG. Kinoshita, T. Haketa, Y. Maeda, H. Fukuhara, G. 10.1039/D1SC00664AChem. Sci.20211266916698 …”
Section: Key Referencesmentioning
confidence: 99%
“…[3][4][5][6] Pioneering work from Lehn and co-workers showed temperature-dependent single-double helix switching based on oligoamides while retaining their lehanded helical sense. 7 Other external stimuli, e.g., solvent, 8-10 light, [11][12][13][14][15] and guest molecules [16][17][18][19][20] have also been shown to regulate single-double helix switching. However, most of these studies have focused on the interconversion between single and double helical forms, and controlling changes in the helical sense along with these processes remains a challenge.…”
Section: Introductionmentioning
confidence: 99%
“…7 Other external stimuli, e.g. , solvent, 8–10 light, 11–15 and guest molecules 16–20 have also been shown to regulate single–double helix switching. However, most of these studies have focused on the interconversion between single and double helical forms, and controlling changes in the helical sense along with these processes remains a challenge.…”
Section: Introductionmentioning
confidence: 99%